A study of ritual communication in Kadayan community in Sarawak - Magiman, Mohamad Maulana; Nordin, Mohd Norazmi (Universitatea Babes-Bolyai, Catedra de Filosofie Sistematica, 2021)
Makan Tahun is a ritual practice performed by the Kadayan community in Sarawak to celebrate the new year. This ritual is performed at the end of the year in December by the Kadayan community, who practice Islam, Pangan, and Christianity. The concern is how a culture with a wide variety of religious beliefs finds a solution in traditions that have been passed down through generations and inherited before any religion existed. During the execution of this ritual, various items were utilized as symbols for transmission which has unknown meanings beyond the group of practitioners. Therefore, this study aims to find out the meaning from the perspective of ritual transmission and symbols utilized in the execution. Ethnographic methods were used in data collection at the study location in Sebuti District, Sarawak. The informants involved in this research are religious experts and ritual practitioners. In-depth interviews with practitioners of the Makan Tahun ritual were conducted in 2018. Data is gathered through the compilation of interview transcripts and the structuring of themes to ensure that each interview is analyzed and interpreted from the perspective of the ritual practitioner community. According to the ethnographic method used, the Makan Tahun is regarded as a ritual to express gratitude for the sustenance provided in the current year. This ritual is performed in the hopes that the giver will multiply the sustenance for the following year. The spirit of tolerance is demonstrated when the Makan Tahun ritual is executed with an element of syncretism, and the entire ritual is guided by people who have a high level of religious understanding and hold social status as religious leaders in the community.